2007
DOI: 10.1007/s11224-007-9223-5
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-directed copper(І) azide coordination polymers bridged by N-donor ligands with different lengths: azide exhibits a rare μ−1, 1, 3, 3 bridging mode

Abstract: A Ligand-Directed strategy has been adopted to synthesize three novel Copper(I) coordination polymers, [Cu 2 (bpe)(N 3 ) 2 ] n (1), [Cu 2 (bpy)(N 3 ) 2 ] n (2), and [Cu 4 (py) (N 3 ) 4 ] n (3), by the reactions of NaN 3 with bpe, bpy and py (bpe = 1,2-trans-(4-pyridyl)ethene, bpy = 4,4 0 -bipyridine, py = pyrazine) in the presence of H 3 PO 3 under hydrothermal conditions, which proved that the length of ligands had subtle effects on overall network and the coordination mode of azide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Studying the influence of the co-ligands on the bridging modes of the azido groups may help us better understand and control the topologies of the azido-bridged complexes. Moreover, the l 1,1,3 -bridging mode of the azido groups in the copper(II) complexes is very rare; to date, there were only a few other l 1,1,3 -azido-bridged copper(II) complexes that have been reported [7][8][9][10][11][12][13][14]. Thus, more work needs to be done to design and construct new polynuclear complexes with l 1,1,3 -azido bridges.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the influence of the co-ligands on the bridging modes of the azido groups may help us better understand and control the topologies of the azido-bridged complexes. Moreover, the l 1,1,3 -bridging mode of the azido groups in the copper(II) complexes is very rare; to date, there were only a few other l 1,1,3 -azido-bridged copper(II) complexes that have been reported [7][8][9][10][11][12][13][14]. Thus, more work needs to be done to design and construct new polynuclear complexes with l 1,1,3 -azido bridges.…”
Section: Introductionmentioning
confidence: 99%
“…The last in this issue is a communication by Fan et al [353] who report on the hydrothermal syntheses and crystal structures of three copper(I) azide coordination polymers, [Cu 2 (bpe)(N 3 ) 2 ] n , [Cu 2 (bpy)(N 3 ) 2 ] n and [Cu 4 (py)(N 3 ) 4 ] n (bpe = trans-1,2-di-(4-pyridyl)ethene, bpy = 4,4 0 -bipyridine, py = pyrazine). It was shown that the structures of the complexes changed from 2D to 3D networks upon reducing the lengths of the bridging ligands.…”
Section: Issuementioning
confidence: 96%